Deadliest enemies : law and the making of race relations on and off Rosebud Reservation - Biolsi, Thomas, 1952- (University of California Press, 2001)
Racial tension between Native American and white people on and near Indian reservations is an ongoing problem in the United States. As far back as 1886, the Supreme Court said that "because of local ill feeling, the people of the United States where [Indian tribes] are found are often their deadliest enemies.